Ecological Civilization Construction and Tourism Development: A Case Study of the Wuling Mountain Area in Western Hunan, China - Li, Yangkuo; Chen, Jia; Wei, Xiaoqing; Tian, Robert Guang (Advances in Social Sciences Research Journal, 2022)
Ecological civilization construction is a new urban development concept, while tourism is a resource-saving and environment-friendly industry. The study of the coordinated development between ecological civilization construction and tourism is of great practical significance. Taking the Wuling Mountain area in western Hunan, China, as an example, the entropy weight method and TOPSIS method are used to score the ecological civilization construction system and the tourism industry. A coupling coordination degree model is constructed to analyze the relationship between ecological civilization construction and tourism development. The results show that the Wuling Mountain Region in western Hunan Province showed a lag in tourism development from 2017 to 2019. The coupling coordination degree between ecological civilization construction and the tourism industry is slightly imbalanced. A coordinated pattern of ecological environment construction and tourism development should be accelerated.